" Impact of human resources management strategies on organizational behavior Case Study of "The Royal Jordanian Geographical Center - Alzu'bi, Feras Ali Khalefh; al hunaiti, Ahmad Yousef Ali (Journal of Economic, Administrative and Legal Sciences, 2019)
This study aimed to measure the impact of human resources management strategies in terms of their dimensions (employment strategy, evaluation Performance strategy, Training strategy, and compensation strategy) on the levels of organizational behavior in terms of the (individual, group and the organization levels) in the Royal Geographical Center. The study population consists of all employees in the geographical center reached (195) employee, The study selected a simple random sample Included (130) employees, The results of the study showed that there is a statistically significant effect of human resources management (employment strategy, evaluation Performance strategy, and compensation strategy) in organizational behavior with a high degree, And there are no a statistical impact of the (training strategy) on organizational behavior, The results of the study also found that the arithmetical averages and the significance of the dimensions of organizational behavior in the Jordanian Royal Geographical Center were high and in Relative ratios, The study recommended that the senior management in the geographic center should be committed to giving human resource management strategies the Extremely importance, especially the Training strategy, The study also confirmed to increasing attention of the geographic center on organizational behavior at the individual level.
Keywords: human resources; organizational behavior; geographical position